The management of desmoid tumours at Groote Schuur Hospital: A retrospective review of current practice - Pickard, Henri Du Plessis (Division of General Surgery, 2020)
Background: Desmoid tumours (DTs) are rare soft tissue tumours that do not metastasise but are locally aggressive. Management options are varied and the response to treatment can be unpredictable. Aim: The aim of this study was to describe the clinical presentation, management strategies and outcomes for adult patients who were treated for DT. Setting: The study was conducted at Groote Schuur Hospital in Cape Town, South Africa and all patients from 2003 to 2016 who presented with DT were included. Method: This was a retrospective review of records. Data collected included: demographics, DT-associated conditions, site and size of tumour, histological findings, treatment modalities, follow-up and outcomes. Results: Seventy patients with histologically confirmed DT were identified. The majority were women (86%) and 77% presented with a painless mass. The commonest site was the anterior abdominal wall (47%). Definitive surgery was performed in 46 (66%) patients, whereas 13 (19%) had definitive radiotherapy. Nine patients received adjuvant radiotherapy post-surgery for involved or close margins. Recurrence developed in 20% patients post-surgery. In the primary radiotherapy group, one patient had disease progression. Two patients with mesenteric DT died because of bowel obstruction. Conclusion: This retrospective review of patients affected by DT at a single centre demonstrates the rarity of the condition, the unpredictable natural history and the variety of treatment options available. Many of our findings are similar to other published studies, except the mean size of DT which was bigger. Treatment outcomes following surgery or radiotherapy seem acceptable, although study limitations are noted.